A reconfiguração do livro ilustrado infantil: construção de leitores e leituras interativas nos e-picturebooks - Caldas, Ana Carolina Medeiros (2019)
The introduction of mobile computing devices in 21st century culture has generated new practices and experiences in reading habits in contemporary society, especially in the new generation (digital natives). The well-known e-books now open space for one more possibility provided by the improvement of the tablets and smartphones, which are the e-picturebooks, influenced by the emergence of the electronic literature allied to the potentialities of the digital children's literature, as well as theories of the illustrated book or picturebook theory. This research, therefore, investigated how cyberculture has re-appropriated the media illustrated children's book and reconfigured its structure and dimensioning from remediation, new media and interart studies, presenting as general objective the construction of readings operations and the profile of the reader in the Digital Age. The qualitative, bibliographical, exploratory and explanatory methodology brought together diverse sources, among academic materials, books and digital publications to support the ideas presented here. In order to exemplify the object of study in the light of new media, we investigate the awarded works, between the years 2015 and 2017, within the awards of the biggest events in children's literature and the world and national illustrated book, namely: Bologna Ragazzi Digital Award and Jabuti Infantil Digital Award. In this way, we relate traces of the theories of cyberculture to the profile of the children's cyber-reader and to the new operations of reading, providing clues to how contemporary society has experienced reading at the beginning of this century.